Feasibility and Acceptance Testing of a Mobile Application Providing Psychosocial Support for Parents of Children and Adolescents With Chronic Pain: Results of a Nonrandomized Trial. (11th March 2019) - Seidman, Laura C; Martin, Sarah R; Trant, Meredith W; Payne, Laura A; Zeltzer, Lonnie K; Cousineau, Tara M; Donovan, Elizabeth
Abstract: Objective To conduct a single-arm pilot study assessing the feasibility and acceptability of a 30-day parent-focused mindfulness and psychosocial support mobile app intervention for parents of children with chronic pain. Methods Thirty parents completed the intervention, which included a mindfulness curriculum, peer support videos, and written psychoeducational content. Twelve healthcare providers also assessed the app and provided feedback. Feasibility was assessed by server-side documented usage on ≥50% of the days in the intervention period and completion of ≥70% of the mindfulness content. Parent and provider acceptance were assessed by ≥70% of participants rating each acceptance test question as ≥5 on a 7-point Likert scale. Parents completed measures of solicitousness, stress, mindful parenting, and resilience prior to and following the intervention. Results Feasibility results were mixed: parents completed mindfulness content on an average of 11.2 days during the intervention period, slightly under the pre-established criterion. However, parents completed an average of 72.1% of the content, which met feasibility criterion. Acceptance criteria were met for the majority of parent acceptance test questions and all of the provider acceptance test questions. Exploratory analyses of the psychosocial measures revealed significant decreases in parental solicitous behavior and perceived stress, and a significant increase in mindful parenting. Conclusions The current study extends the emerging body of research on mindfulness-based interventions for parents of children with chronic illness and suggests that it may be acceptable to deliver this content through a mobile device. Future research is needed to assess the intervention's efficacy compared to standard of care.